Implementation of the Sanitation Hygiene Policy at the Taliwang Slaughterhouse (RPH) West Sumbawa Regency as a Requirement for Healthy Meat Production - Azmy, Isnia Nurul; Yamin, Ahmad; Dharmawansyah, Dedy (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Slaughterhouses (RPH) must be able to provide safe, healthy, whole and halal (ASUH) meat for the community and implement hygiene and sanitation in every process. The aim of this research is to describe the implementation of sanitation hygiene policies at the Taliwang RPH as a requirement for healthy meat to be consumed by the community. Observations on the implementation of sanitation hygiene policies at the Taliwang RPH were carried out through a process of interviews, observation and documentation with informants with four key variables that influence the success of policy implementation, namely communication, resources, disposition and bureaucratic structure. The results show that the communication that has been built from policy makers to implementers in the field is clear and has been running well with sufficient human resources, but non-human resources such as budget and facilities are still limited. The disposition variable related to attitudes shows that each party supports and provides a positive attitude towards the policy. Meanwhile, regarding the bureaucratic structure, this policy has been supported by the availability of SOPs as a guide to ensure policies are implemented systematically.